Photonic packaging sourcebook fiber-chip coupling for optical components, basic calculations, modules - Fischer-Hirchert, Ulrich H. P. (Springer Berlin Heidelberg, 2015)
Serves as a guide on photonic assembly techniques. It provides an overview of today's state-of-the-art technologies for photonic packaging experts and professionals in the field. The text guides the readers to the practical use of optical connectors. It also assists engineers to find a way to an effective and inexpensive set-up for their own needs. In addition, many types of current industrial modules and state-of-the-art applications from single fiber to multi fiber are described in detail. Simulation techniques such as FEM, BPM and ray tracing are explained in depth. Finally, all recent reliability test procedures for datacom and telecom modules are illustrated in combination with related standardization aspects.